Students’ Ability in Writing English Argumentative Essay - Hikmah, Durratul; Khoir, Farrah Maulida Nadia (International Journal of English Education and Linguistics (IJoEEL), 2023)
Learning to write has a significant impact on determining the ability and quality of students in academic activities. One form of essay featured in academic writing is the argumentative essay. Writing an argumentative essay leads students to explore their opinions or arguments to convince the reader. Nevertheless, some studies show that college students face some difficulties in writing argumentative essays. Hence, the purpose of this study was to investigate the students’ ability to write argumentative essays in terms of essay structure. A qualitative case was used in this study. The data was taken from the final test of the Advance Writing course written by 36 fourth-semester students of the English Language Education Program. The research findings showed that most students’ ability to write an argumentative essay is well developed, with a result of 31%. The result indicated that the students knew how to write an argumentative essay based on its structure, but they still made some mistakes dealing with sentence structure and the credibility of the references used.